2023
DOI: 10.2174/1573397118666220610123242
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome in Behçets Disease Patients: Keep an Eye on the Eye

Abstract: Background: Metabolic syndrome (MetS) is characterized by insulin resistance, high blood pressure/sugar, dyslipidemia, and obesity. Whether MetS and its components affect the development of Behçet's Disease (BD) remains unclear. Aims: The aim was to determine the frequency of MetS among BD patients and to study its relation to the disease characteristics. Methods: The study included 1028 adult BD patients recruited from 18 specialized rheumatology centers. 51 healthy matched control were considered. Behçet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The results of the nine trials including 35,648 patients, also demonstrated an increased OR for hypertension in association with BD [ 27 , 30 , 32 38 ]. The meta-analysis revealed a significant association between BD and hypertension (pooled OR 1.39; 95% CI 1.13–1.70; P = 0.002), with considerable heterogeneity ( I 2 = 65%; P = 0.003; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of the nine trials including 35,648 patients, also demonstrated an increased OR for hypertension in association with BD [ 27 , 30 , 32 38 ]. The meta-analysis revealed a significant association between BD and hypertension (pooled OR 1.39; 95% CI 1.13–1.70; P = 0.002), with considerable heterogeneity ( I 2 = 65%; P = 0.003; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies recorded triglyceride levels [ 22 29 , 31 , 34 , 35 , 38 ], and nine studies recorded high-density lipoprotein (HDL) levels [ 22 28 , 34 , 38 ] in patients with BD. The meta-analysis illustrated that elevated triglyceride levels were not significantly related to BD (MD, 9.36; 95% CI −1.96–20.68; P = 0.11; Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Behçet's disease (BD) is a multi‐systemic inflammatory disorder associated with a wide variability of unpredictable clinical manifestations ranging from mild mucocutaneous lesions to severely morbid or life‐threatening conditions like central nervous system involvement, blindness, large vessel vasculitis and perforation of the gastrointestinal tract 1,2 . High disease activity for long periods together with the long courses of treatment with immunosuppressive drugs may lead to permanent organ damage with high morbidity and poor disease outcomes 3,4 . Discrimination among disease activity and damage is crucial for proper disease management and avoidance of unnecessary increase in immunosuppressive treatment 5,6 …”
Section: Introductionmentioning
confidence: 99%
“…1,2 High disease activity for long periods together with the long courses of treatment with immunosuppressive drugs may lead to permanent organ damage with high morbidity and poor disease outcomes. 3,4 Discrimination among disease activity and damage is crucial for proper disease management and avoidance of unnecessary increase in immunosuppressive treatment. 5,6 Accordingly, The Outcome Measures in Rheumatology (OMERACT) has emphasized that assessment of both BD activity and damage are mandatory, separate and complementary items in the BD outcome measures.…”
Section: Introductionmentioning
confidence: 99%